Environmental Management System in UAE : A Review - Veera Kumar, Mohan; Lau, Seng; Tonga, Noweg (Kalpana Corporation, 2020)
In the global world, to manage the working activity as per the environmentally friendly initiative, every manufacturing industry must perform tasks to protect the environment. It is regarded as a major concern for the industrial sector. In respect to this, various manufacturing industries highly adopt the “Go Green” initiative and prefer to implement environmental management system so that they will be able to make a proper balance between their operational activity and environmental-friendly initiative. The study mainly focuses on the environmental management system in the UAE by evaluating and overcoming the challenges of its implementation among the manufacturing industries. The study identifies the need and current status of the manufacturing industries in the implementation of the environmental management system, especially in Abu Dhabi. The study also identifies and analyses the key drivers and challenges which are related to the implementation of the environmental management system. It also includes the literature which mainly focuses on awareness of environmental management system, its effectiveness and development to overcome the challenges in the implementation of the environmental management system. At last, the study also describes the finding and discussion based on the collective facts so that effective conclusion and recommendation will be provided effectively.